Explorations in giftedness - Sternberg, Robert J.; Jarvin, Linda; Grigorenko, Elena L. (Cambridge University Press, 2010)
"This book is a scholarly overview of the modern concepts, definitions, and theories of intellectual giftedness, and of past and current developments in the field of gifted education. The authors consider, in some detail, the roles of intelligence, creativity, and wisdom in giftedness and the interaction between culture and giftedness, as well as how giftedness can be understood in terms of a construct of developing expertise. The authors also review and discuss a set of key studies that address the issues of identification and education of children with intellectual gifts. This volume may be used as a summary overview of the field for educators, psychologists, social workers, and other professionals who serve intellectually gifted children and their families"-- Provided by publisher